1637 : the coast of chaos - Flint, Eric; Hasseler, Bjorn (Novelist) (Ring of fire (Riverdale, N.Y.), 2021)
"Europe, 1632. It is a time of upheaval and great change. But none so great as when an unexplained temporal and spatial phenomenon known as the Ring of Fire transports the blue collar town of Grantville, West Virginia, smack dab in the middle of the Thirty Years War. When the dust settles, it becomes clear that the town of Grantville isn't going anywhere, and the can-do Americans of the twenty-first century begin altering the course of history forever. It is now five years later, and the effects of the Ring of Fire reach from the Old World to the New. But the course of exploration and colonization will look much different than it did in our timeline. The French bought the English possessions in North America way back in 1633, but have never done much with the uncivilized backwater. Until the new king of France, Gaston I, decides that it's time to seize the territory and establish French control over it. Here then, a new anthology, edited by Ring of Fire series creator Eric Flint, chronicling the exploits of the citizens of Grantville, their allies, and their enemies, as they venture forth onto a new continent"--